On the Role of English as a Foreign Language Learners’ Individual Differences in Their Use of Grammar Learning Strategies - Li, Shaoru (Frontiers in Psychology, 2022)
As the use of strategies facilitates the tedious process of language learning, a multitude of studies have been conducted on language learning strategies and their educational consequences. Nonetheless, grammar learning strategies (GLSs) have not been widely studied. Moreover, no review study has been carried out to illustrate the role of individual differences in the use of GLSs. To address the existing gaps, the present review study intends to explain the role of English as a foreign language (EFL) learners’ individual differences (i.e., desire to learn a second language, motivation, and willingness to communicate) in their employment of GLSs. The favorable impact of individual difference variables on grammar learning strategy use were proved using the theoretical and empirical evidence. Future research directions and pedagogical implications are also discussed.